Leadership and crisis - Jindal, Bobby (Blackstone, 2010)
In his new book, Louisiana Governor Bobby Jindal reveals the extent of the Obama administration?s incompetence during the BP oil spill and shows why common sense conservative solutions are exactly what we need to solve our nation?s biggest problems.
Keywords: Jindal, Bobby, 1971-